Kecekapan pengurusan bank komersil tempatan di Malaysia berasaskan model kecekapan Farrell - Viky Novriza Prima Putra ,; Shaharir Mohamad Zain, (Penerbit ukm, 2006)
It is shown that based on the Farrell overall efficiency index as formulated by Aly et al. (1990), on average, for local commercial banks in Malaysia in 2001 is about 90%. This is higher than the same efficiency index for banks in USA, Italy, Croatia and Taiwan studied by various scholars in 1990-2002. The inefficient banks are Affin Bank, Public Bank, RHB, Bumiputra-Commerce Bank, Eon Bank and Alliance Bank Malaysia, in the increasing order of Farrell efficiency of the banks. Other Farrell efficiency measures show that every local commercial Malaysian bank is efficient. These results show that the Farrell efficiency model is not suitable for ranking the local commercial banks in Malaysia